The Quality of Life in Polish Cities with Poviat Rights - Sarzyński, Konrad (Journal of Public Governance, 2021)
Objectives: The study aims to measure the quality of life in cities with poviat rights and analyse whether differences depend on the number of city residents. Research Design & Methods: It was hypothesised that the greater the number of inhabitants, the higher the quality of life in a given city. This hypothesis was verified with calculations based on the Statistics Poland data in the form of synthetic and auxiliary indicators. Findings: The results confirmed the hypothesis. The highest scores characterise the largest Polish cities regarding health, ecology, and economic and social spheres. Simultaneously, it was the smallest cities with poviat rights that had the highest security and education levels. Implications / Recommendations: All cities with poviat status need to improve ecological awareness, as it is an area with the lowest scores regardless of the size of the city. Contribution / Value Added: The presented model uses commonly accessible data and is easy to replicate, although it might give less precise results than a custom-made analysis. Article classification: research article JEL classification: I31